Simulation and optimization of a Concentrating Solar Power Plant with Thermal Energy Storage in Sebha city by using system advisor model (SAM) - Sharif, Mohamed Alamen; hossin, Mohamad; Al-Hashmi, Salem A. (Journal of Pure & Applied Sciences, 2021)
Concentrated solar power (CSP) is viewed as one of the most promising alternatives in the field of solar energy utilization; parabolic trough collector (PTC) solar power plants are the most commercially established among the power plants operating with CSP technology. In this paper, a parabolic trough solar thermal power plant with thermal energy storage was evaluated in terms of design and thermal performance, using the SAM program of NREL (System Advisor Model). This program is used to evaluate the active and economic performance of a plant such as monthly energy production, annual energy production, and level cost of energy (LCOE).one representative site in south Libya, Sebha city, which offers an annual average direct normal radiation (DNI) of more than 6.0 kWh/m2/day, has been chosen for the analysis and optimization of the proposed 100 MWe PTC Solar power plant. The optimization is carried out with solar multiple (SM) and full load hours of thermal energy storage TES as the parameters, to minimize the Levelized cost of electricity and maximize the annual energy yield. Based on the findings of the study, the proposed 100 MW PTC solar power plant with thermal energy storage can contribute to the sustainable energy future of Libya with reduced dependency on fossil fuels. This design and performance analysis of the plant encourages further development and innovation of solar thermal power plants in all regions of Libya.